Cultivating Vegetable Plants in Pots to Introduce Environmental Education for Elementary School Students: Budidaya Tanaman Sayuran dalam Pot Dalam Rangka Mengenalkan Pendidikan Lingkungan Untuk Siswa Sekolah Dasar - Prastyaningsih, Sri Rahayu; Azwin, Azwin; Sri Wahyuni (Universitas Lancang Kuning, 2024)
SD TQ Anas bin Malik is an elementary school established by the Anas bin Malik Foundation in 2022 by the Anas Foundation. SD TQ Anas Bin Malik focuses students on Islamic education based on the Quran and As-Sunnah. Learning activities were carried out in several houses in a complex rented by the Foundation. As a new school, school facilities are still fewer. The children also do not yet have extracurricular activities. The cultivation of vegetable plants in pots is a solution for extra-curricular activities. Community Empowerment activities held on Friday, January 12, 2024, at 07.00 WIB until it is over. There are 18 participants who combination of classes IV, V, and VI. The results of activities that have been successful are socialists on the cultivation of vegetable plants in pots, plant, and evaluation of plant growth.